Sumber Informasi Kesehatan Ibu Hamil di Indonesia Selama Masa Pandemik Covid 19 - Maria Lupita Nena Meo; Lenny Ganika (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2021)
Background: Barriers to accessing maternal and child health services was the impact of the covid 19 pandemic. This causes obstacles in accessing health information for pregnant women.Objective: This research aims to track the sources of information that were most often used by pregnant women during the COVID-19 pandemic and the level of satisfaction of mothers with the sources of information used.Method: This study was a quantitative study with a cross-sectional survey design conducted in 7 islands in Indonesia. The number of respondents who participated in this study were 350 pregnant women who were recruited using random sampling technique. Data were collected online using a questionnaire and analyzed using descriptive analysis. Result and Discussion: The results showed that 46.3% of respondents used social media platforms as a source of health information used during the COVID-19 pandemic and 48.8% of respondents stated that they were not satisfied with the sources of information used.Conclusion: The social media platform is the most sought after by pregnant women in Indonesia as a source of health information during the covid 19 pandemic. The use of internet-based health education media must become an alternative to meet health information needs Keywords: accessing health information; covid 19 pandemic; pregnant women